Hybrid solar desalination system for generation electricity and freshwater with nanofluid application: Energy, exergy, and environmental aspects - Rafiei, A. (Elsevier Ltd, 2022)
In this investigation, a hybrid energy conversion system is proposed and evaluated for energy, exergy, and environmental criteria for generating power and freshwater. The system comprises of a Humidifier Dehumidifier Desalination (HDD) system for producing freshwater, an organic Rankine cycle system for generating electric power, and a solar Parabolic Trough Concentrator for absorbing solar energy as the desalination heat source. Different working fluids including Al2O3, Cu, CuO, TiO2, and MWCNT nanoparticles in oil as the base fluid are examined. The influence of different nanofluids on the performance of the system is investigated as the main goal of this study. Environmental impacts of the suggested system are studied. Results show that the thermal efficiency of the Parabolic Trough Concentrator was with the application of Cu/oil nanofluid as about 62.4. It is illustrated that the amount of freshwater production can be increased by raising the nanofluid concentration. The freshwater production varies between nearly 15.28 kg/h to 15.46 kg/h with the application of nanofluid. The organic Rankine cycle net work and total efficiency improved with increasing nanofluid concentration. Also, it can be concluded that the application of MWCNT/oil with a concentration of 5 volume fraction has shown the highest exergy efficiency of 4.7. It was concluded the suggested desalination system with application of the solar organic Rankine cycle system, in addition to producing fresh water and power, significantly reduced amounts of CO2 emissions in the environment. Finally, it should be mentioned that the ideal system was analyzed and the gains from the use of nanofluids are very small. Â© 2021 Elsevier Ltd